Confiança, desempenho e conformidade de memória: impactos no sistema jurídico-criminal brasileiro - Weslley Santos Sousa (2024)
Human memory is a dynamic and constructive process that is susceptible to various internaland external influences. In this context, a person reporting high confidence in a particular memory may not be entirely accurate. Understanding the complex relationship between confidence and memory accuracy is crucial, in part, because of its many practical implications in the criminal justice context, where the degree of confidence and accuracy of witnesses can determine the overall procedural dynamics. Several factors can influence this relationship, making confidence a crucial element in the interpretation of memory accuracy. Here, we present three original articles that explore the complex relationship between confidence and memory performance and its practical implications for everyday legal-criminal proceedings. The first article provides an overview of the variables that influence the relationship between confidence and memory performance and discusses their implications for the justice system. It emphasizes the complexity and the need for caution in interpreting confidence as an indicator of accuracy. The second article analyzes how testimonies are collected and individuals are identified in Brazil, pointing out the main difficulties that have prevented the establishment of evidencebased protocols in the Brazilian criminal justice system. Finally, in the third article, we report three experiments that investigate how the phenomenon of memory conformity affects the recognition of human faces and the recall of spatial contexts. Together, these three articles provide a comprehensive understanding of the influences on memory accuracy and confidence. Furthermore, the articles present elements that can help improve practices in the legal and criminal justice systems, advancing the understanding of the various factors that can impact human memory.